Trimethoxyflavones from Ocimum basilicum L. leaves improve long term memory in mice by modulating multiple pathways. (15th September 2022) - Singh, Varinder; Kaur, Kiranpreet; Kaur, Sanimardeep; Shri, Richa; Singh, Thakur Gurjeet; Singh, Manjinder
Abstract: Ethnopharmacological relevance: Traditionally, Ocimum basilicum L. leaves (OB) are recommended for various brain disorders. Aim of the study: Scientific evidence highlights the cognition improvement capacity of Ocimum basilicum L. leave extract (OBE), however, the compound(s) responsible for this effect and the associated mechanism was not reported. The present study was, thus, designed to isolate and identify the compound responsible for memory improvement effects of OB and to delineate the associated mechanism of action. Materials and methods: In-vitro acetylcholinesterase (AChE) inhibitory (Ellman method) and antioxidant (DPPH scavenging) assays guided fractionation was employed to isolate the bioactive compounds from OBE. The isolated compounds were characterised using spectroscopic techniques (FTIR, NMR and MS). In-silico and in-vivo [mouse model of scopolamine (SCOP) induced amnesia] investigations were used to substantiate the memory improvement effects of isolated compounds and to understand their mechanism of action. Results: AChE and DPPH assays guided fractionation of OBE lead to isolation of two pure compounds namely, 5, 7-dihydroxy-3′, 4′, 5′-trimethoxyflavone (S1) and 3-hydroxy-3′, 4′, 5′-trimethoxyflavone (S2). Both S1 and S2 mitigated the cognitive impairment due to SCOP in mice by reducing brain AChE activity, TBARS, TNF-α, IL-1β, IL-6 and caspase-3 concentrations and elevating reduced glutathione and IL-10 levels; together with amelioration of brain hippocampus histopathological aberration (H and E staining). Moreover, the molecular docking of S1 and S2 at the active pockets of AChE and caspase-3 has shown good interactions with vital amino acid residues. Conclusions: Our findings show that trimethoxy flavones are responsible for the memory improvement effect of OBE due to their anticholinergic, antioxidant, anti-inflammatory and anti-apoptotic properties. These maybe developed as valuable alternatives for management of cognitive disorders. Graphical abstract: Image 1